1998
DOI: 10.1111/j.1095-8649.1998.tb00812.x
|View full text |Cite
|
Sign up to set email alerts
|

Conventional karyotype, nucleolar organizer regions and genome size in five Mediterranean species of Syngnathidae (Pisces, Syngnathiformes)

Abstract: Conventional karyotypes, NOR-bearing chromosomes by means of silver impregnation and genome size were investigated in five Mediterranean species in three genera of the Syngnathidae. A karyotype of 48 subtelocentric-acrocentric chromosomes was found in the seahorse Hippocampus hippocampus (FN=48) while a diploid value of 44 occurred in H. guttulatus (2 sm-m+42 a; FN=46) and the pipefish Syngnathus abaster (44 a; FN=44) and S. typhle (44 a; FN=44). The pipefish Nerophis ophidion, possessing a diploid chromosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 14 publications
5
20
0
Order By: Relevance
“…Our phylogeny suggests that the primary split between these two lineages occurred at the same time or shortly before the major morphological radiation of male brooding structures and subsequent radiation of species (Wilson et al 2001). The early diversification of the ancestral syngnathid into tail and abdominal brooders is consistent with results from a karyotypic study, which highlights a possible total-genome duplication in the abdominal-brooding lineage (Vitturi et al 1998). Brooding structures within these two lineages independently increased in complexity, culminating in the completely enclosed brood pouches located on the tail of seahorses (Herald 1959; type A5) and the well-defined abdominal pouch of Oostethus brachyrus (type B3), the most complex abdominal pouch type.…”
Section: Mitochondrial Phylogeny Supports Parallel Evolution Of Majorsupporting
confidence: 76%
“…Our phylogeny suggests that the primary split between these two lineages occurred at the same time or shortly before the major morphological radiation of male brooding structures and subsequent radiation of species (Wilson et al 2001). The early diversification of the ancestral syngnathid into tail and abdominal brooders is consistent with results from a karyotypic study, which highlights a possible total-genome duplication in the abdominal-brooding lineage (Vitturi et al 1998). Brooding structures within these two lineages independently increased in complexity, culminating in the completely enclosed brood pouches located on the tail of seahorses (Herald 1959; type A5) and the well-defined abdominal pouch of Oostethus brachyrus (type B3), the most complex abdominal pouch type.…”
Section: Mitochondrial Phylogeny Supports Parallel Evolution Of Majorsupporting
confidence: 76%
“…According to Schmidt (1978: in Vitturi et al, 1998, a single pair of NORbearing chromosomes represents a primitive condition in most vertebrate species. It is difficult to make comparisons within Batrachoidid species since no reports including data on NORs for toadfish are available.…”
Section: Resultsmentioning
confidence: 99%
“…The same study found evidence for a ZW sex chromosome system in a more distantly related stickleback species, Apeltes quadracus (Chen and Reisman 1970). In contrast, no heteromorphic sex chromosome pairs have been reported in the outgroup family Syngnathidae (Vitturi et al 1998;Libertini et al 2006). The existence of different sex chromosome systems within the stickleback family, along with the availability of genetic resources and the complete genome sequence of the female threespine stickleback (Peichel et al 2001;Kingsley et al 2004;Kingsley and Peichel 2007) make this fish a compelling vertebrate system in which to study sex chromosome evolution.…”
Section: S Imple Genetic Sex Determination (Gsd) In Which Amentioning
confidence: 96%